Income, Poverty and Charcoal Production in Western Uganda - Khundi, Fydess; Jagger, Pamela; Shively, Gerald; Sserunkuuma, Dick (United States Agency for International Development (USAID), 2010)
Uganda faces all too typical development challenges, including widespread poverty, low rates of labour absorption and stagnant agricultural growth. As a result, the country suffers from ongoing problems associated with land and forest degradation as poverty perpetuates extractive activities with low returns and often forces families to deplete natural capital. Charcoal production is broadly representative of the pressures facing mixed-use forests in developing regions. In many countries the charcoal trade represents one of the largest domestic industries, with some estimates showing that it eventually could rival cash crops in terms of overall employment. Yet, alarming projections of damages associated with charcoal production underscore the environmental havoc it can cause.